COVID-19 and the potential long-term impact on antimicrobial resistance - Rawson, Timothy M; Moore, Luke S P; Castro-Sanchez, Enrique; Charani, Esmita; Davies, Frances; Satta, Giovanni; Ellington, Matthew J; Holmes, Alison H (Journal of antimicrobial chemotherapy, 2020)
Abstract The emergence of the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) has required an unprecedented response to control the spread of the infection and protect the most vulnerable within society. Whilst the pandemic has focused society on the threat of emerging infections and hand hygiene, certain infection control and antimicrobial stewardship policies may have to be relaxed. It is unclear whether the unintended consequences of these changes will have a net-positive or -negative impact on rates of antimicrobial resistance. Whilst the urgent focus must be on controlling this pandemic, sustained efforts to address the longer-term global threat of antimicrobial resistance should not be overlooked.